ANALISIS DAN PERANCANGAN WEBSITE PENDATAAN KELAHIRAN DAN KEMATIAN PENDUDUK DESA PURWAWINANGUN KABUPATEN CIREBON - Agus Sevtiana; Wiwiek Nurkomala; Indah Noeryanti (Jurnal Digit, 2018)
Abstract The development of Information Technology is currently very rapid with the existence of a service and means of information is very important especially for people who are in the City and in the Village. One of the utilization of information technology in the form of application of birth data and death of Purbawinangun web-based residents, to facilitate data collection of birth and death rate. Data collection of births and deaths occurring in Purbawinangun Village has many problems in the processing of birth and death data that have been manually recaptured, making it difficult to know the fluctuation of population development from year to year, data collection is only done from the information of citizens who report to the Village Head. application data collection of birth and death web-based created using the programming language PHP and MySql software as data storage media. It provides information on reports of population, birth and death data presented in bar charts and can display reports of population data, web-based birth and death data. The system running in Purbawinangun Village is still less effective in data collection of birth and death. So the author will create an application that can record the data birth and death computer to facilitate the recording and create reports from the application itself. Keywords: Application, Data Collection, Population, Birth, Death.